Tinjauan Yuridis Pelakasanaan Perkawinan Walian Tondo (Turunan Raja) Berdasarkan Hukum Adat Kulisusu Utara Kabupaten Buton Utara - Laode Haniru (Jurnal Hukum Volkgeist, 2017)
Marriage aims to form a happy family and everlasting. Marriage requires careful consideration in order to persevere in the long periods of time in a relationship as husband and wife. Indispensable attitude of tolerance and put yourself on the proper role. One example of such marriages, i.e. marriage down the bed. Marriage down bed (Walian tundra) frequently took place in the area of North Buton to the culture. Therefore, researchers are interested in writing a research on the status and validity of the marriage bed down according to customary law. (studies in North buton). In this study the author uses the method of normative legal research i.e. research approach the problems and legal norms in force. Legal norms that apply to that form of positive written legal norms such as the Constitution, laws, government regulations and so on. Research results show that implementation of the marriage walian tondro (down bunks) based on customary law Kulisusu Sub-district in Waode village of Buri North Kulisusu can occur if the following: a) the already existing agreement of husband and wife when the wife is still alive, that when I died (wife) then you (the husband) must be married with the sister of girs as a substitute for the mother of our children and this should be known to be mutually agreed by both parties in defense. In the sense that there must be a will from the wife. b) after it is accepted then the two sides will carry out walian tondro (mate's bed). C) Covenant of marriage anniversary match existing Covenant of marriage (islam). D) wedding reception. There are several reasons underlying the onset of mating walian tondro (down bed) so that the wife can provide replacements for descendants as the legitimate successor of the family.